Content Analysis of analysis of Institute for Information Studies’ publications: pilot study - Seljan, Sanja (2009)
The authors present the results of the pilot study of language and content analysis of Institute for information studies’ publications. Aim of the research is to gain knowledge into the usage of terminology (frequency, collocations etc.), chronological appearance of terminology, and penetration of cited resources (issuing date compared with date of citation) in the 19 publications from 1990 to 2009. Since the project aims to continue backwards, the pilot study presents the results of the analysis of the most recent publication "Digitization".